2021
DOI: 10.3390/biomedicines9121890
|View full text |Cite
|
Sign up to set email alerts
|

The Visceral Adiposity Index in Non-Alcoholic Fatty Liver Disease and Liver Fibrosis—Systematic Review and Meta-Analysis

Abstract: (1) Background: In order to avoid a liver biopsy in non-alcoholic fatty liver disease (NAFLD), several noninvasive biomarkers have been studied lately. Therefore, we aimed to evaluate the visceral adiposity index (VAI) in NAFLD and liver fibrosis, in addition to its accuracy in predicting NAFLD and NASH. (2) Methods: We searched PubMed, Embase, Scopus, and Cochrane Library, identifying observational studies assessing the VAI in NAFLD and liver fibrosis. QUADAS-2 was used to evaluate the quality of included stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 91 publications
(164 reference statements)
2
20
0
Order By: Relevance
“…Emerging evidence suggests that fatty liver indices might be associated with indices of atherosclerosis [ 24 , 25 , 26 ]. The visceral adiposity index (VAI) and metabolic score for visceral fat (METS-VF) are novel estimates of intra-abdominal fat content and cardio-metabolic health [ 27 , 28 ]. In addition, there is a validated surrogate of body composition-derived adiposity called the body adiposity index (BAI) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that fatty liver indices might be associated with indices of atherosclerosis [ 24 , 25 , 26 ]. The visceral adiposity index (VAI) and metabolic score for visceral fat (METS-VF) are novel estimates of intra-abdominal fat content and cardio-metabolic health [ 27 , 28 ]. In addition, there is a validated surrogate of body composition-derived adiposity called the body adiposity index (BAI) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence revealed that the accumulation of visceral adipose tissue was a strong predictor of the occurrence of NAFLD. In the case of similar body weight, people with a higher proportion of visceral fat were more prone to develop NAFLD (23,24). In this study, the visceral adipose tissues in the model group markedly increased and the morphology of epididymal adipose tissue was abnormal mainly characterized by the expansive sizes and irregular shapes of adipocytes.…”
Section: Effects Of Green Teas On Visceral Adipose Tissuementioning
confidence: 52%
“…On the other hand, epididymal adipocytes in the different green tea groups were significantly smaller and had more regular shapes compared with the model group.Increasing evidence revealed that the accumulation of visceral adipose tissue was a strong predictor of the occurrence of NAFLD. In the case of similar body weight, people with a higher proportion of visceral fat were more prone to develop NAFLD(23,24). In this study, the visceral adipose tissues in the model group markedly increased and the morphology of…”
mentioning
confidence: 48%
“…In a study comprised of 142 NAFLD patients, liver biopsies were conducted, and visceral adiposity index was used as a clinical measurement with the assessment of serum levels of different cytokines. The study found the independent correlation of insulin resistance and visceral adiposity index with significant fibrosis in NAFLD [113] . A review of 24 studies reported the visceral adiposity index as a predicting factor in the diagnosis of NASH and NAFLD and a higher value of visceral adiposity index in NAFLD patients as compared to persons without NAFLD [114] .…”
Section: Correlation Of Sarcopenia and Nafldmentioning
confidence: 71%